KAJIAN INTERAKSI OBAT PADA PENGOBATAN DIABETES MELITUS (DM) DENGAN HIPERTENSI DI INSTALASI RAWAT JALAN RSUD UNDATA PERIODE MARET-JUNI TAHUN 2014 - Ida Nurlaelah; Alwiyah Mukaddas; Ingrid Faustine (Universitas Tadulako, 2015)
One of the chronic complications of diabetes mellitus is a disorder of macrovascular as hypertension so that in it’s medicinal treatment required therapy with multiple drugs all at once that can lead to drug interactions. Drug interactions can result in increased toxicity and decrease the effectiveness of drugs that interact. This study aims to determine the prescription profile of DM patients with hypertension include the number of drugs prescribed, dosage forms, classes and types of drugs and the incidence of drug interactions theoretically, based on the mechanism drug interactions in outpatient installations of RSUD Undata Palu 2014. This design research is a non-experimental study with descriptive. Retrieval of patient data performed prospectively during the period from March to June 2014. Subjects who fill the inclusion criteria is adult patients that attain age of 18-60 years and diagnosed diabetes mellitus with hypertension are interview to obtain primary data while the secondary data such as medical records and prescriptions. Retrieved 61 sample. Based on dosage forms prescribe profile that most often given to the DM patients with hypertension was tablets (94.5%). Class of diabetes drugs most widely used is a sulfonylurea (21.1%) and hypertension drug classes beta blocker (12.2%). Types of diabetic drugs most widely used was glimepiride (14.2%) and hypertension was bisoprolol (9.2%). The percentage result of drug interactions theoretically was 85.2% (52 patients), drug interactions type that the most occured was pharmacodynamic interactions 72.7%. Diabetes melitus Patients with hypertension in outpatient installations of RSUD Undata Palu 2014 were most potentially subjected to drug interactions